CFD STUDY OF A MICRO AIR VEHICLE (MAV) - Shern, L.Y.; Mohd Sa’at, F. A. Z; Abdul Wahap, A. (Journal of Mechanical Engineering and Technology (JMET), 2022)
Micro Air Vehicle (MAV) is new type of aircraft technology that is maturing day by day and have recently reached unprecedented levels of growth. MAV is small in size and provides enormous potential in many applications, both for military and civilian use. There are three types of MAV, namely rotary wing, flapping wing and fixed wing. Due to the small size, MAV faces difficulty to fly properly due to the atmospheric perturbations. This study aims to model a suitable fixed wing MAV using Computational Fluid Dynamics (CFD) to investigate the lift coefficient, drag coefficient and lift to drag ratio when MAV is used in pertubed flow conditions. When there is wind disturbance, the simulation results show that the lift and drag coefficient for several angle of attack changes. However, the lift to drag ratio seems unaffected. Results showed that MAV is best operated at 8° angle of attack as it provided the maximum lift to drag ratio for situations without and with the present of wind disturbances. The fluid dynamics behavior of flow around MAV are also discussed accordingly. Even though MAV is small in size, it is found that vortex or vorticity flow also exist in MAV, especially at high degree angle of attack.